ACACia java peer-to-peer knowledge sharing application - Bolido, Chasky J.; Lee, Aldwin Philip C.; Lorica, Cheryl V.; Rosales, Arnel B. (2003)
Today, more than ever, we are experiencing rapid changes in almost every aspect of human development, the most tangible of which is in terms of economic development. Still, many countries, like the Philippines, are left behind by other countries in these economic advancements. Clearly, there is something in these more progressive economics that the slower economies have failed to recognize. The answer perhaps lies in the idea of Knowledge Economy, where knowledge is now being utilized as an abundant, zero marginal cost capital, which small economies can exploit through the creation of knowledge-enhanced products, and the promotion does not deplete, but grows with use, and thus, our country, which is scarce in other resources but teeming with people who have the potential to establish a knowledge-base, through a cheap and convenient venue where people can learn and share information. The ACACia Knowledge Sharing Application is a Java-based peer-to-peer (PSP) application which facilitates a user (help request)-peer/expert (feedback) mechanism using the new open source technologies, JXTA, Thinlet, and Hypersonic SQL Database Engine. Each peer's shared database grows with information from other peers, producing redundancy which increases the availability of the information and the speed of the search system. ACACia is still limited to answering technical questions, in particular, those pertaining to computer systems and to information and communications technology, but is developed to accomodate other topics materials easily. The initial knowledge content of the system will come from experts in the field. Later on, users can lend their own knowledge simple by adding them to their databases. In effect, all users become experts which is the goal of the system.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Distributed databases; Information storage and retrieval systems; Peer-to-peer architecture (Computer networks).; JXTA (Computer network protocol).; ACACia (Computer program).